Anticorpos antieritrocitários: prevalência e especificidade em transplantados renais, doadores de sangue e pacientes com insuficiência renal crônica - Angulo, Ivan de Lucena (1997)
A quite different pattern of antierythrocytic antibodies was found in kidney-transplant recipients, normal blood donors and chronic renal failure patients undergoing hemodialysis and multitransfused. Kidney transplants with the same donor s ABO/Rh blood groups have low prevalence of antierythrocytic antibodies of immune type. As they are not transfused, may be exposed to fetal antigens during pregnancy. Natural antibodies could be raised by bacterial estimulus enhanced by immunosupression. Autoantibodies were found in those receiving cyclosporin, perhaps as a feature of autoimmunity by the drug. Normal blood donors have the same prevalence of natural and immune-type antibodies. Women predominate and as they were not transfused, pregnancy was the most probable stimulus again. CRF patients in São José do Rio Preto are aloimmunized against red cell antigens less frequently than other studies and have no anti-N like or -Nf, as they are not exposed to formaldehyde. Women with antibodies of immune type predominate again, probably stimulated by fetal antigens. More sensitive and specific methods will help us understand antierythrocytic antibodies production under exposure to blood group antigens in healthy and immunossupressed people under different stimulus.